Microglial Priming and Alzheimer’s Disease: A Possible Role for (Early) Immune Challenges and Epigenetics? - Hoeijmakers, Lianne; Heinen, Yvonne; van Dam, Anne-Marie; Lucassen, Paul J.; Korosi, Aniko (Frontiers in Human Neuroscience, 2016)
Neuroinflammation is thought to contribute to Alzheimer’s disease (AD) pathogenesis that is, to a large extent, mediated by microglia. Given the tight interaction between the immune system and the brain, peripheral immune challenges can profoundly affect brain function. Indeed, both preclinical and clinical studies have indicated that an aberrant inflammatory response can elicit behavioral impairments and cognitive deficits, especially when the brain is in a vulnerable state, e.g. during early development, as a result of aging, or under disease conditions like AD. However, how exactly peripheral immune challenges affect brain function and whether this is mediated by aberrant microglial functioning remains largely elusive. In this review, we hypothesize that; 1) systemic immune challenges occurring during vulnerable periods of life can increase the propensity to induce later cognitive dysfunction and accelerate AD pathology, and 2) that 'priming' of microglial cells is instrumental in mediating this vulnerability. We highlight how microglia can be primed by both neonatal infections as well as by aging, two periods of life during which microglial activity is known to be specifically upregulated. Lasting changes in (the ratios of) specific microglial phenotypes can result in an exaggerated pro-inflammatory cytokine response to subsequent inflammatory challenges. While the resulting changes in brain function are initially transient, a continued and/or excess release of such pro-inflammatory cytokines can activate various downstream cellular cascades known to be relevant for AD. Finally, we discuss microglial priming and the aberrant microglial response as potential target for treatment strategies for AD.